ANALISIS PENGARUH INDIKATOR MAKROEKONOMI DAN INDEKS SAHAM REGIONAL ASEAN TERHADAP PASAR SAHAM INDONESIA (IHSG) PERIODE PADA TAHUN 2009-2014 - Immanuel, Roisondo; Satria, Dias (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study was intended to know and analyze the fluctuations of macroeconomic indicators and stock index regional ASEAN and the correlation with Jakarta Composite Index (JCI) at Indonesian Stock Exchange. and The macroeconomic indicators represented by inflation, exchange rate (Rupiah to Dollar America) and BI Rate. Stock index regional ASEAN represented by STI which represents Singapore stock-market, KLSE which represent Malaysia stock-market, SET which representsThailand stock-market and PSE which represents Filippine stock-market. This is quantitative research and the research method used Error Corection Model (ECM). The sampling data used are 72 months from the beggining year of 2009 until the end year of 2014. The result of the study shows that simultaneously the macroeconomic indicators and stock index regional ASEAN has significant effect on Jakarta Composite Index at short-term and long-term, but in partially inflation and BI Rate at short-term has no effect on Jakarta Composite Index however at long-term has significant effect on Jakarta Composite Index. While exchange rate (Rupiah to Dollar America) at short-term and long-term has significant effect on Jakarta Composite Index. For stock index regional ASEAN, STI at short-term and long-term has no effect on Jakarta Composite Index. While KLSE, SET and PSE at short-term and long-term has significant effect on Jakarta Composite Index. Â Keywords : JCI, Inflation, Exchange Rate, BI Rate, STI, KLSE, SET, PSE, Error Corection Model